IMPACT OF PHYSICAL ACTIVITY ON ANXIETY LEVELS IN ADULTS - PHN, ARSHPREET KAUR, BSN, RN; OCS , RASIKA BHIDE, PT, MS (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Anxiety disorders rank among the most common mental health issues globally, profoundly affecting individual well-being and social productivity. Individuals aged 20 to 40 years constitute a significant demographic, since this phase includes critical life transitions such as professional development, family creation, and social role solidification, which frequently increase susceptibility to anxiety (Henriksson et al., 2021). Even though drugs and therapy are still common ways to treat mental health problems, more and more evidence points to physical activity as an effective, easy-to-administer alternative. This paper looks at how structured physical exercise affects anxiety levels in young and middle-aged adults. It achieves this by synthesizing the available evidence, proposing a theoretical model, and outlining methodological approaches that can inform practice.